PENGGUNAAN APLIKASI PTV VISSUM PADA EVALUASI KINERJA JALAN KAWASAN TAMAN BUKIT GELANGANG - Risno nainggolan (Jurnal TeKLA, 2023)
The city of Dumai is an area that is currently carrying out activities such as the construction of the Dumai Islamic Center and the Lepin market, and some are already operating, such as a culinary village, Taman Bukit Arena, and Ramayana. With these places, it can increase the volume of traffic that is on Jalan Jawasan Taman Bukit Gelanggang. From the existing problems, an evaluation of road performance is carried out, whether the road is still able to accommodate the increase in traffic volume that has occurred. The purpose of this study was to determine the performance of roads and intersections based on the 2014 Indonesian Road Capacity Guidelines (PKJI) and modeled using the PTV Vissum 22 application. From the results of the evaluation carried out, it was found that DJ was on Jalan Sudirman 0.19, which with a DJ value of that size, the road was still safe and far from traffic jams. After the simulation was carried out using the PTV Vissum 22 application, the road that experienced the most traffic movement was Jalan Raya Bukit Datuk.